Biological response to lyophilized demineralized dentin matrix implanted in the subcutaneous tissues of rats - Felipe Andretta Copelli; Antonio Adilson Soares de Lima; Carolina Carvalho de Oliveira Santos; Everdan Carneiro; Bruno Cavalini Cavenago (Saudi Dental Journal)
Aim: Lyophilized demineralized dentin matrix (LDDM) consists of a type 1 collagen complex matrix containing growth factors and no mineral crystals. Although the efficacy of LDDM for bone grafting is well known, there is limited evidence on the biological response to human lyophilized DDM. Therefore, the aim of this study was to evaluate the biological response of subcutaneous tissues in rats to powdered LDDM, mineral trioxide aggregate (MTA), and Biodentine implanted using polyethylene tubes. Methods: Forty Wistar rats were divided into four groups (n = 10 each) depending on the experimental time intervals and were placed in polyethylene tubes containing LDDM, MTA, biodentine, and one empty control. After 3, 7, 15, and 30 observation days, the animals were sacrificed and quantitative and qualitative analysis of the subcutaneous tissue samples was carried out. The intensity of the inflammatory response was scored from 0 (no response) to 3 (severe response), and the data were statistically analyzed using ANOVA and Bonferroni tests (p < 0.05). Results: All groups exhibited moderate inflammation after 3 and 7 days of observation, with presence of inflammatory infiltrate predominantly consisting of macrophages and angioblastic proliferation being observed. After 15 observation days, the control group exhibited mild inflammation and a predominance of fibroblasts, and this differed significantly from the remaining cement groups that exhibited moderate inflammation. After 30 days of observation, all groups exhibited a mild inflammatory response, predominance of fibroblasts, and a greater amount of collagen fibers. Conclusion: Within the limitations of this study, it can be concluded that LDDM exhibited an acceptable biological response similar to MTA and Biodentine in the subcutaneous tissues of rats.